HUBUNGAN ANTAR BEBERAPA UNSUR IKLIM MIKRO PADA PRODUKSI TANAMAN KARET ( Hevea brasiliensis) KLON PB260 - Kresna Shifa Usodri; Dimas Prakoswo Widiyani; Dedi Supriyatdi (Jurnal AGROSAINS dan TEKNOLOGI, 2022)
This study aims to examine the relationship between microclimate and production of rubber plants at planting age in 2004, 2005, 2006, and 2007 at PTPN 7 Way Berulu Business Unit. The research was conducted from September 2019 to March 2020 at PTPN 7 Way Berulu Business Unit, Afdeling 1. The study was conducted from September 2019 to March 2020. The research location was at PTPN 7 Way Brulu Business Unit in Afdeling 1, Negeri Katon, Pesawaran. The tools and materials used in this research are stationery, camera, raffia, meter, thermohygrometer, and Lux meter. This study uses the basic method of quantitative and qualitative descriptive analysis (descriptive analysis). Data were collected, compiled, explained, then analyzed by correlation analysis and multiple linear regression which were described descriptively. Multiple linear regression analysis technique was used to determine the functional effect between the dependent variable and the independent variable. The dependent variable is influenced by the independent variable and is denoted by Y. The dependent variable in this study is rubber production (tonnes), while the independent variable is the variable that affects or causes the change in the dependent variable and is denoted by X. The results show that in each of the observed microclimates have a positive correlation with each other ; Light, temperature, and humidity are interrelated with each other in influencing the level of latex production of rubber clones Pb260.